Analisis Komparatif Produktivitas Tanaman Aren di Kabupaten Lima Puluh Kota - Calista, Mila Quinsy; Wulandari, Eliana; Karyani, Tuti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Lima Puluh Kota Regency has a strong economic foundation in the agricultural sector, with sugar palm (Arenga pinnata) as its primary commodity. Sugar palm trees are widely distributed across 10 sub-districts, but the concentration of sugar production is centered in Lareh Sago Halaban, Mungka, Gunuang Omeh, Bukik Barisan, and Suliki sub-districts. This study aims to analyze the differences in sugar palm productivity among these five sub-districts. Data on productive land area and palm sap production from 2019 to 2023 were obtained from the Central Statistics Agency (BPS) of Lima Puluh Kota Regency as secondary data for this study. The hypothesis regarding a significant difference in productivity between sub-districts testes using a One-Way ANOVA analysis.. The results showed a significant difference in productivity between Mungka Sub-district and Gunuang Omeh Sub-district. However, no significant differences were found in other sub-districts. Nevertheless, the average production of palm sap varied among the five sub-districts.